ASSESSING POTENTIAL PROBLEMS IN CUSTOMER SERVICE OF PT. XYZ - Kusumawati, Desy; Siallagan, Manahan Parlindungan Saragih (Journal of Business and Management, 2017)
Abstract. The development of the game industry, growing drastically by the end of 2014 where demand for hardware and games itself is increasing. Of course, in every process of production and innovation, game developers can not be separated from the role of the customer or player game. The information that come from the customers or game players are quite important because customers who are enjoy and feel certain games, so what is delivered by the customer will affect the improvement in the next version of particular games. Customer service is part of the company that has a role as a bridge between the company and the customers. PT. XYZ, as one of game developers in Indonesia was almost bankrupt because they did not understand the customers’ wants and needs. They just developed the game what they liked. This is a big loss for companies because they did not get enough information about what the customers or game players review about the games. Because of the situations is ever happened in PT. XYZ, the risk management in the customer service division might be able to reduce the generated loss because of the potential problems in the future. This research was conducted in the customer service department of PT. XYZ to find out the cause of the problems that exist in that section. So, by understanding the prioritization of each problem, it is expected to reduce the impact of the losses that may arise. The results of the data analyzed in this study are AHP calculations, which quantifies the problem to understand the level of urgency in each issue using Expert Choice software as the tool. AHP has a high level of preference and expert taste or respondents. It might be having various results, depending on each respondent. Based on the data analysis, there are 14 issues that could potentially pose a customer service risk. Too many media aspirations become the highest frequency and impact that will occur. It is expected that this research can be used to find out the problems that can affect the company and cause damage. The author hopes in further research, this research will develop, not only in customer service but also throughout the company. Keywords:Assessing Problems, Games, Customer Service, AHP, Prioritized Problems